Village fund accountability and gendering in Masculine Hegemonic Institution: A study during COVID-19 - Fitriani, Desti; Shauki, Elvia R; Pratiwi, Siti Czafrani (UI Scholars Hub, 2020)
The study is aimed to evaluate accountability and gender roles in enhancing the accountability of village fund and other government-related assistance during COVID-19 pandemic. This study employed an integrated framework of accountability, gender socialization theory and gender subtext theory. This study applies a case study with 2 (two) types of instruments, i.e., observations and semi-structured interviews. The villages observed have provided limited information regarding the BLT DD assistance and other COVID-19 related assistance. Consequently, the villagers did not have sufficient information to participate in the village decision-making process and to criticize BLT DD assistance and other COVID-19 related assistance distribution process. The villagers were not invited to any village meetings that it prevents them to provide inputs and consequences to the village government. As a result, the level of accountability regarding the information provided, a discussion held and consequences are given at a minimum level. The roles of female BPD members were insignificant due to the pervasiveness of gendering practice in village organizations. These findings contradict gender socialization theory that women with all their feminine traits are suitable and potential to perform supervisory tasks in guiding the organization. However, these findings are aligned with gender subtext theory that segregation of duties based on masculinity and femininity are apparent in the village organization.